THE CHARACTERISTICS OF BIOACTIVE PEPTIDES AND ANTIBACTERIAL ACTIVITY OF HONEY BEE (Apis nigrocincta) SMITH VENOM, ENDEMIC TO SULAWESI - Mokosuli Yermia Semuel; Rudi Alexander Repi (Molekul, 2015)
Apis nigrocincta Smith is a species of honey bee cavity nesting, endemic to Sulawesi. Research that aims to find the composition of the bioactive content of peptides and antibacterial activity of honey bee venom A. nigrocincta Smith has been conducted. Honey bee venom composition was analyzed using Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) Method and Spectrophotometer UV-Vis Method. Analysis of antibacterial activity, was conducted using a modified agar diffusion method. The results showed that the venom of the honey bee Apis nigrocinctaSmith has five bands of molecules with a molecular weight i.e. 33.54kDa; 21 kDa and 15.43 kDa. The peptide detected were hyaluronidase, fosfolipase A, mellitin, lysofosfolipase or antigen 5. Antibacterial activity was higher than the control ampisilin and antibiotic streptomycin.